ANALISIS DEIKSIS DALAM NOVEL KAMI (BUKAN) SARJANA KERTAS - Yeni Nuryanti Wadu Kadja; Labu Djuli; Margareta P.E.Djakaho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is entitled "Deixis in the Novel We (are not) Paper Graduates by J.s Khairen. The problem in this research is how is the use of deixis in the novel We (are not) Paper Graduates by J.s Khairen?. This research aims to describe the use of deixis in the novel We (are not) Paper Graduates by J.s Khairen. This type of research is library research using descriptive methods, meaning analyzing the data found descriptively. Data collection in this research uses reading and note-taking techniques. Data analysis is carried out using a pragmatic approach with several stages, namely identifying, classifying data, analyzing data and concluding the results of data analysis. Based on the results of the data analysis that has been done, 390 data were found consisting of 299 personal deixis data, 42 place deixis data, and 49 time deixis data. The forms of personal deixis found are the form of I, me, we, us, you, you, he and they. The forms of place deixis are here, there, here and there. The forms of time deikis namely yesterday, now, tomorrow and in the future.